An investigation about the genotoxic activities of some herbal teas used as folk medicine - (:unkn) unknown (My University, 1997)
In this research the genotoxic activities of some herbal teas used as folk medicine were investigated by the umu-test using a tester strain Salmonella typhimurium TA 1535/pSK 1002 carrying the umuC-lacZ fused gene with (+S9) and without (-S9) metabolic activation. The induction of umu gene expression was monitored by measuring the cellular β-galactosidase activity produced by fusion gene using a colorimetric method. Consequently, from 10 herbal teas used in this research, only two of them showed weak genotoxicity.
Keywords: Genotoxicity; Herbal teas; Umu test